The Effect of Palladium Training on Some of the Kinematic Variables of the Stage of Improvement and Achievement of Long Jump Effectiveness - Hanoun Dagger Saadi, Ahmed; Abdulaaima Kadhim Alsaedi, Mazin; Mohsen Saadoun, Hussein; Hussein Hameedi, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to prepare plyometric exercises and identify the level of some of the kinematic variables for the stage of upgrading for the members of the research sample, identify the level of achievement among the members of the research sample, and identify the impact of plyometric exercises on some kinematic variables. As for the research hypotheses, there was a statistically significant effect of plaque-leaving exercises on some kinematic variables. As for the research fields, the human field included the Maysan governorate team for the youth category in the long jump, while the temporal field was taken for the period from 10/3/2018 to 20/5/2018, while the spatial field was the playground of the Scout Camp for the Education of Maysan. The research methodology and its field procedures included the experimental method, which was used for its suitability with the nature of the research. The research sample reached ten ) jumpers representing the Maysan team for the youth category in the long jump.